Managing and understanding behavior problems in Alzheimer's disease and related disorders - Teri, Linda; Lurie, James; University of Washington. Instructional Media Service (Seattle: University of Washington, 1990)
(producer) A training program for caregivers responsible for day-to-day care or supervision of dementia patients. It is designed to: provide background information about Alzheimer's disease and related disorders, including the current state of research, clinical evaluation, and treatment; teach caregivers skills to assess and modify behavior problems which interfere with proper care; and identify and address the special needs of caregivers. Modeled after behavioral techniques used successfully with other groups, materials teach caregivers to think about problems as happening in a sequence of ABC (Antecedents/triggers; Behavior; and Consequences/results.) Using the sequence, caregivers design a plan for change and learn how to deal with common troubling behaviors in dementia.
1. Overview. Part 1, Alzheimer's disease and related diseases (17 min., 33 sec.) 2. Overview. Part II, Delirium and depression (15 min., 25 sec.) 3. ABCs, an introduction (15 min., 10 sec.) 4. Managing aggressive behaviors, anger and irritation, catastrophic reactions (18 min., 58 sec.) 5. Managing psychotic behaviors, language deficits (8 min., 9 sec.) 6. Managing psychotic behaviors, hallucinations/ delusions and paranoia and suspiciousness (13 min, 51 sec.) 7. Managing personal hygiene, bathing and dressing (13 min.) 8. Managing difficult behaviors, wandering and inappropriate sexual behaviors (16 min.) 9. Managing difficult behaviors, depression (21 min., 40 sec.) 10. Caregiver issues (32 min., 32 sec.)
Videorecording is avaitable at Koleksi Media, Perpustakaan HUKM
Title on cassete label: Managing & understanding behaviour problems in Alzheimer's disease & related disorders.
Supported in part by a grant from the National Institute on Aging to the University of Washington, Alzheimer's Disease Research Center (1P50-AG5316-01A1)
Co-producers, James Lurie and Linda Teri
Keywords: Alzheimer Disease -- videocassettes; Behavior Theraphy -- methods -- videocassettes; Caregivers -- videocassettes; Dementia -- videocassettes